Modeling Conversion Strategies for Regional Banks to Islamic Banks Using the Analytic Network Process (ANP) Approach - Syahril Hamid; Tatik Mariyanti; ⁠Nirdukita Ratnawati (Politeknik Siber Cerdika Internasional, 2026)
Background: Islamic banking in Indonesia has grown for over two decades; however, its market share remains below 8%, and the spin-off scheme of Islamic Business Units has demonstrated limited effectiveness. Converting Regional Development Banks (BPD) into Islamic Commercial Banks offers a strategic alternative, yet an integrated conversion model combining technical, organizational, and sharia dimensions is still lacking, using Regional Development Banks (BPD) in Indonesia as the research object. Objective: This study formulates a holistic conversion model by identifying priority problems, solutions, and strategies for converting BPD into Islamic Commercial Banks. Methods: This study employed the Analytic Network Process (ANP) combined with the Tawhidy String Relation (TSR)framework. Internal factors were mapped using the McKinsey 7S framework, while external factors covered legality, regulation, and customer aspects. Data were collected through in-depth interviews and pairwise-comparison questionnaires distributed to seven purposively selected experts, comprising regulators, sharia banking practitioners, and academics with direct conversion experience. ANP analysis was performed using SuperDecisions v.3.2 software, with a consistency ratio (CR) ≤ 0.10. Results: Strategy emerged as the most dominant internal problem (geomean = 0.40), driven by the absence of an integrated sharia transformation strategy. The priority solution is strengthening strategy through business and market-potential studies. The top recommended strategy is forming a dedicated sharia licensing team, supported by legal consultants and benchmarking with previously converted banks. Conclusion:Successful conversion of BPD into Islamic Commercial Banks is largely determined by strategic readiness as the foundation for sustainable, sharia-aligned transformation, supported by a roadmap integrating maqashid sharia into corporate governance.